Risk-based evaluation of the vulnerability of the Skagerrak–Kattegat marine fish community to Swedish fisheries. (23rd October 2020) - Hornborg, Sara; Hobday, Alistair J; Borthwick, Louisa; Valentinsson, Daniel
Abstract: Progress towards ecosystem-based fisheries management calls for useful tools to prioritize actions. To select suitable methods for local circumstances, evaluating approaches used in other jurisdictions can be a cost-effective first step. We tested Productivity Susceptibility Analysis (PSA) to assess the potential vulnerability of the marine fish community in the Skagerrak–Kattegat (Eastern North Sea) to possible interactions with all Swedish fisheries operating in the area. This analysis combines attributes for a species productivity with attributes related to the susceptibility to capture to quantify a single score for vulnerability: high, medium, or low risk. Results indicate that demersal trawl and gillnet fisheries were associated with the highest risk levels if interaction occurs, i.e. having the highest prevalence of species with potentially high vulnerability to the fisheries. Mixed results were seen when comparing the assessment results with available data. The main benefit of utilizing PSA in the area is the comprehensiveness of the assessment, including data-deficient fisheries and species. Drawbacks include potential overestimation of actual risks. Overall, together with available data, PSA in the studied area provides a comprehensive map of potential risks for further actions and may progress a science-based, precautionary management of the area.